Implementation of Phenomenon-based Learning E-Module to Improve Critical Thinking Skills in Thermochemistry Material - Bella Pratiwi*; Jimmi Copriady; Lenny Anwar (Jurnal Pendidikan Sains Indonesia, 2021)
The covid-19 pandemic in Indonesia has affected various sectors, one of them is in the education sector. Thus, it interferes with the learning processes conventionally. A solution is needed to respond to the problem in the 21st century. Online learning is one of the alternative ways in utilizing the use of IT-based teaching materials. This study aims to improve the students’ critical thinking skills by using an e-module. The research was the quantitative descriptive method. This study was a quasi-experimental by using a nonequivalent control group design. The samples of the study consisted of 2 classes, namely XI MIPA 1 and XI MIPA 2. The analysis results using independent sample t-test showed a significance value of 0,000 0,05. The data analysis results of critical thinking skills used N-gain score test; the experimental class obtained a score of 0,72, in which it belonged to the high category. Meanwhile, the average N-gain score for the control class was 0,34, in which it belonged to the medium category. It can be concluded that there is a significant difference in the students’ critical thinking skills between the experimental class and the control class. Therefore, the implementation of a phenomenon-based learning e-module can be an alternative to improve the students’ critical thinking skills.